Evaluation of triple negative breast cancer with heterogeneous immune infiltration - Quintana, Ángela; Arenas, Enrique Javier; Bernadó, Cristina; Navarro, José Fernández; González, Jonatan; Esteve-Codina, Anna; Moliné, Teresa; Marti, Merce; Curigliano, Giuseppe; Schmid, Peter; Peg, Vicente; Arribas, Joaquín; et al. (Frontiers in Immunology, 2023)
Introduction Tumor infiltrating lymphocytes (TILs) are known to be a prognostic and predictive biomarker in breast cancer, particularly in triple negative breast cancer (TNBC) patients. International guidelines have been proposed to evaluate them in the clinical setting as a continuous variable, without a clear defined cut-off. However, there are scenarios where the immune infiltration is heterogeneous that some areas of the patient’s tumour have high numbers of TILs while other areas completely lack them. This spontaneous presentation of a heterogeneous immune infiltration could be a great opportunity to study why some tumours present TILs at diagnosis but others do not, while eliminating inter patient’s differences. Methods In this study, we have identified five TNBC patients that showed great TIL heterogeneity, with areas of low (≤5%) and high (≥50%) numbers of TILs in their surgical specimens. To evaluate immune infiltration heterogeneity, we performed and analyzed bulk RNA-sequencing in three independent triplicates from the high and low TIL areas of each patient. Results Gene expression was homogeneous within the triplicates in each area but was remarkable different between TILs regions. These differences were not only due to the presence of TILs as there were other non-inflammatory genes and pathways differentially expressed between the two areas. Discussion This highlights the importance of intratumour heterogeneity driving the immune infiltration, and not patient’s characteristics like the HLA phenotype, germline DNA or immune repertoire.